TINJAUAN KUALITAS SUNGAI BENGKENANG BERDASARKAN FISIKA KIMIA PERAIRAN DAN KOMUNITAS MAKROINVERTEBRATA - Abdul Rahman Singkam; Agus Budi Utomo; Bhakti Karyadi (Universitas Lambung Mangkurat, 2022)
This research aims to determine the quality of Bengkenang River based on the physicochemical factors and macroinvertebrates community. The measuring of physicochemical parameters was carried out at three stations, namely Sukarami Village, Durian Seginim, and Padang Burnai with two periods for each station: April 2019 following the peak of the rainy season and September 2019 following the peak of the dry season. The physicochemical factors were analyzed descriptively, while macroinvertebrates community were analyzed as the indices of Shannon-Wiener diversity index (H’), Ephemeroptera-Plecoptera-Trichoptera (EPT), and Family Biotic (FBI). The temperature, dissolved oxygen, degree of acidity, and total dissolved solids of this river in each station were in the normal range. This study found 611 individuals of macroinvertebrates that were divided into 21 species (21 families; 4 phyla; 5 classes). The highest species abundance was Epeourus aculeatus, 22.42% of the total sample. The H’ index from up- to downstteram were 1.79; 2.03; 1.80 respectively, indicating the Bengkenang River is slightly to moderately degraded. The total number of EPT individuals was 305, with mostly found at the downstream and dominated by Heptaginidae (Ephemeroptera). The FBI values were 3.81; 4.18; and 4.33 showed that the quality of the water is “very good”. Based on this physico-chemical factors, H’, EPT, and FBI data, it can be concluded the Bengkenang River is in a good quality.